Gender on Wall Street Uncovering Opportunities for Women in Financial Services - Mattia, Laura (Springer International Publishing, 2018)
This book contains advice and direction for women who are either seeking a career or who have already embarked on a career in financial services. The book first aims to help the female reader gain clarity on her motivation in pursuing a career in finance. It then identifies potential gender-specific challenges that could create problems if she is unaware or unconscious to her surrounding work environment. Lastly, it provides insights and exercises to develop a strategy for career accomplishment. Written by a former Senior Financial Executive for several fortune 500 firms including M&M Mars, a Wealth Manager/Owner of a fee-only Registered Investment Advisory firm, and Professor of financial planning at the University of South Florida, the book will help women identify pitfalls, create game plans to transcend the limitations of their workplace cultures, and learn how to collaborate with their peers to create healthier work environments. Told through personal stories, anecdotes from other women and academic research, Gender on Wall Street helps women identify the internal and external obstacles to their success. This book will also provide a means of overcoming these obstacles through conscious engagement, personal reflection and strategy-building exercises at the conclusion of each chapter. The reader will be guided into creating their own personal career plan-the STAR plan-which will help them achieve career success.